Pemanfaatan AI (Artificial Intelligence) Dalam Pembuatan Media Pembelajaran - Ita Handayani; Widyah Noviana; Harumi Widihastuti (AMMA : Jurnal Pengabdian Masyarakat, 2024)
The purpose of the dedication to the community is to provide training in creating learning media using AI (Artificial Intelligence) to enhance the creativity of teachers. The dedication to this community is carried out in the State Department of Rawakalong 03. Methods of implementation of dedication to the community, among others: 1) Stage of observation, at this stage is conducted survey of location, survey of problems experienced by the school, and assignment of teachers to be followed include, 2) Stage Pre Training, in this stage teachers are given approval regarding the application used and how to create the account, 3) Stage Training, on this stage the teacher is given training making learning media in power point and quiz using AI (Artificial Intelligence) 4) Stage Discussions, at that stage the dedication team and teachers discuss each other related difficulties in making learning medium in power points and quiz forms 5) Stage Evaluation, dedication Team checks the learning media outcome in powerpoint and quiz already made by the teacher and has been sent to an email to one of the teachers. Results to be achieved in dedication to this community are: 1) adding insights and benefiting State SD teachers Rawakalong 03 for use in learning, 2) power point and quiz using AI (Artificial Intelligence), 3) publication of articles in journals.